Postcard from the Greater New York Councils, Boy Scouts of America - Boy Scouts of America. Greater New York Councils (1943)
Postcard thanking Max Bredig (1902-1977) for his financial support of the Boy Scouts of America.
Keywords: Boy Scouts of America; Boy Scouts of America. Greater New York Councils; Thank-you notes